RAPID DECOMPOSITION OF SOLID WASTE BY ACTINOMYCETE - U. Karthickeya,; T. Sathieshkumar,; K. Soundhirarajan,; Dr. D. Roopa, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2025)
The taxonomic and ecological positions of antibiotic producing actinomycetes are well recognized for their metabolic flexibility, commonly accompanied by the production of primary and secondary metabolites of economic significance. Various approaches including classical, chemo taxonomical, numerical taxonomic and molecular have been routinely employed for the identification of actinomycetes. The metabolic perspective of actinomycetes not only provides an interesting area for research but also offers the possibility of commercialization of the metabolites generated in the process. Enzymes such as amylase, lipase, and cellulases produced from actinomycetes play an important role in food, fermentation, textile and paper industries. Certain enzymes used as therapeutic agents in human cancer, mostly in acute lymphoblastic leukemia. Actinomycetes are useful in cancer treatment, bioremediation and it produces some valuable antibiotics such as novobiocin, amphotericin, vancomycin, neomycin, gentamycin, chloramphenicol, tetracycline, erythromycin, nystatin, etc. Actinomycetes are also used as plant growth promoting agents (help to produce plant growth hormone Indole-3-acetic acid), biocontrol tools, biopesticide agents, antifungal compounds, and biocorrosion and as a source of agroactive compounds. Therefore, actinomycetes play a significant role in the production of various antimicrobial agents and other industrially important substances such as enzymes. The potential of actinomycetes in the discovery of novel compounds with activity against microorganisms has been realized, and hence opens exciting avenues in the field of biotechnology and biomedical research.